An evolutionarily conserved gene, FUWA, plays a role in determining panicle architecture, grain shape and grain weight in rice. (August 2015) - Chen, Jun; Gao, He; Zheng, Xiao‐Ming; Jin, Mingna; Weng, Jian‐Feng; Ma, Jin; Ren, Yulong; Zhou, Kunneng; Wang, Qi; Wang, Jie; Wang, Jiu‐Lin; Zhang, Xin; et al.
Summary Plant breeding relies on creation of novel allelic combinations for desired traits. Identification and utilization of beneficial alleles, rare alleles and evolutionarily conserved genes in the germplasm (referred to as 'hidden' genes) provide an effective approach to achieve this goal. Here we show that a chemically induced null mutation in an evolutionarily conserved gene, FUWA, alters multiple important agronomic traits in rice, including panicle architecture, grain shape and grain weight. FUWA encodes an NHL domain‐containing protein, with preferential expression in the root meristem, shoot apical meristem and inflorescences, where it restricts excessive cell division. Sequence analysis revealed that FUWA has undergone a bottleneck effect, and become fixed in landraces and modern cultivars during domestication and breeding. We further confirm a highly conserved role of FUWA homologs in determining panicle architecture and grain development in rice, maize and sorghum through genetic transformation. Strikingly, knockdown of the FUWA transcription level by RNA interference results in an erect panicle and increased grain size in both indica and japonica genetic backgrounds. This study illustrates an approach to create new germplasm with improved agronomic traits for crop breeding by tapping into evolutionary conserved genes.